2021
DOI: 10.3390/antiox10111651
|View full text |Cite
|
Sign up to set email alerts
|

Ozonated Sunflower Oil Exerted Protective Effect for Embryo and Cell Survival via Potent Reduction Power and Antioxidant Activity in HDL with Strong Antimicrobial Activity

Abstract: Ozonated sunflower oil (OSO) has potent antimicrobial effects, making it useful for topical applications to treat various skin diseases. On the other hand, regarding mechanistic insight, the antioxidant activity and cytoprotective effects of OSO are relatively less known. The current study compared the antioxidant ability and protective ability of OSO on cells and embryos against oxidative stress, such as H2O2 and oxidized low-density lipoproteins (oxLDL), to investigate its potential applications for wound-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 42 publications
7
25
0
Order By: Relevance
“…Withal, Liu et al demonstrated that the topical application of a moisturizer formulation containing linoleic acid and ceramides alongside glucocorticoids in patients with psoriasis led to a better maintaining of the stratum corneum hydration and decreased the adverse effects of the topical application of glucocorticoids [ 60 ]. Cho et al substantiated that ozonated sunflower oil has antimicrobial, antioxidant and protective capacities, sustaining the potential usage in cutaneous diseases [ 61 ]. HAO also reduced skin irritation induced by anionic and non-ionic surfactants in vivo, mainly due to the interaction of oil with proteins, which reduced the binding of the surfactants [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Withal, Liu et al demonstrated that the topical application of a moisturizer formulation containing linoleic acid and ceramides alongside glucocorticoids in patients with psoriasis led to a better maintaining of the stratum corneum hydration and decreased the adverse effects of the topical application of glucocorticoids [ 60 ]. Cho et al substantiated that ozonated sunflower oil has antimicrobial, antioxidant and protective capacities, sustaining the potential usage in cutaneous diseases [ 61 ]. HAO also reduced skin irritation induced by anionic and non-ionic surfactants in vivo, mainly due to the interaction of oil with proteins, which reduced the binding of the surfactants [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative electrophoretic mobility depends on the intact charge and three-dimensional structure of HDL. Therefore, for each group, agarose gel electrophoresis with HDL 2 and HDL 3 was carried out in the nondenatured state [ 46 ]. The gels were then dried and stained with 0.125% Coomassie Brilliant Blue, after which the relative band intensities were compared by band scanning using Gel Doc ® XR (Bio-Rad) with Quantity One software (version 4.5.2).…”
Section: Methodsmentioning
confidence: 99%
“…After a few seconds, the stained HDL fraction was blotted onto a Formvar carbon-coated 300 mesh copper grid and air-dried. The shape and size of the HDL particles were determined by TEM at 40,000× magnification, according to a previous report [ 43 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relative electrophoretic mobility depends on the intact charge and three-dimensional structure of HDL. Hence, agarose gel electrophoresis was carried out with HDL 2 and HDL 3 from each group under the non-denatured state [ 41 ]. The gels were then dried and stained with 0.125% Coomassie Brilliant Blue, after which the relative band intensities were compared via band scanning using Gel Doc ® XR (Bio-Rad) with Quantity One software (version 4.5.2) of Bio-Rad (Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…After a few seconds, the stained HDL fraction was blotted onto a Formvar carbon-coated 300 mesh copper grid and air-dried. The shape and size of the HDL were determined by TEM at a magnification of 40,000×, according to a previous report [ 41 ].…”
Section: Methodsmentioning
confidence: 99%